EVALUATION OF BONE HEALING IN FEMURS LENGTHENED VIA THE GRADUAL DISTRACTION METHOD - Jochymek, Jiri; Gal, Petr (Biomedical papers, 2007)
Background: Treatment of leg length inequality via lengthening of the shorter extremity is an infrequent orthopedic procedure due to the requirement of special distraction devices and possible serious complications. Essential qualitative changes in operative technique development are associated with the name of G. A. Ilizarov, who paved the way for the autoregenerate gradual distraction method in the 1950s.Material and Methods: In the years 1990 through 2006 a total of 57 patients underwent femur lengthening via gradual distraction using various types of external fixators at the Department of Pediatric Surgery, Orthopedics, and Traumatology, Faculty Hospital in Brno. The quality of bone healing was monitored and a number of parameters followed and statistically evaluated using regularly scheduled X-ray examinations.Results: In 11 cases we had to remove the external fixator following the distraction phase, perform an osteosynthesis via a splint and fill the distraction gap via spongioplasty. The bone healing was satisfactory in the remaining 46 patients and the lengthened bone required no other fixation method. The analysis showed statistically significant deceleration in bone healing following distraction in female patients over 12 years of age, and in boys over 14 years of age. Lack of periosteal callus five weeks after surgery always signified serious problems in further healing. Severe complications were recorded in 11 cases during the distraction phase, and in 9 cases after the removal of the distraction apparatus.Conclusions: The aim of this report was to present the results of our study of distraction gap bone healing using the gradual lengthening approach.
Keywords: Leg lengthening/Gradual distraction/External fi xation/Leg discrepancy/Complication